2007
DOI: 10.1097/mlg.0b013e3180312380
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Salvage Operation in Head and Neck Microsurgical Reconstruction

Abstract: In this study, we examined salvage operations after reexploration in head and neck reconstruction and analyzed ways to solve problems. Free flap reconstruction of the head and neck lesion was carried out for 513 cases in our hospital over the past 12 years. Twenty-one cases of reexploration were caused by postoperative thrombosis (4.1%). We could only salvage seven cases (33.3%) of 21 cases from flap thrombosis. All seven cases were included in the category of venous thrombosis, and they were undertaken within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…However, in patients for whom airway compromise and fistula formation are less of a concern, discharge by postoperative day 3 may be a safe option. Overwhelmingly, the literature demonstrates that when free flaps fail, the majority do so within the first 48 to 72 hours; furthermore, chances at salvage are greatest during the first 3 days postoperatively . Patients included in this study were monitored until postoperative day 2 on average, at which point the greatest risk of flap failure had passed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in patients for whom airway compromise and fistula formation are less of a concern, discharge by postoperative day 3 may be a safe option. Overwhelmingly, the literature demonstrates that when free flaps fail, the majority do so within the first 48 to 72 hours; furthermore, chances at salvage are greatest during the first 3 days postoperatively . Patients included in this study were monitored until postoperative day 2 on average, at which point the greatest risk of flap failure had passed.…”
Section: Discussionmentioning
confidence: 99%
“…Overwhelmingly, the literature demonstrates that when free flaps fail, the majority do so within the first 48 to 72 hours; furthermore, chances at salvage are greatest during the first 3 days postoperatively. [17][18][19][20][21][22] Patients included in this study were monitored until postoperative day 2 on average, at which point the greatest risk of flap failure had passed. The single flap failure in this group occurred approximately 2 weeks out, at which point salvage was beyond consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Mean re-exploration time for salvage cases was 1.3 days compared with 3.9 days for those not salvaged. (16) Kind et al (17) suggested that a miniature doppler ultrasonic probe attached directly to the outflow vein of the flap may lead to a significant improvement in the salvage rates of free flaps. They identified 20 instances of vascular compromise in 147 free flaps using this technique with a salvage rate of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postoperative complications is high: between 45% and 53.6% of cases, with an occurrence that is correlated to the tumor stage . Functional sequelae are also frequent despite the progress that has been made in head and neck reconstruction . The complications resulting from prior radiotherapy are added to those resulting from the salvage surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Functional sequelae are also frequent despite the progress that has been made in head and neck reconstruction. 8,9 The complications resulting from prior radiotherapy are added to those resulting from the salvage surgery. Therefore, due to the sequelae and a poor prognosis, the majority of patients do not recover their preoperative performance status.…”
Section: Introductionmentioning
confidence: 99%